Análise biomecânica do chute frontal de karatê: implicações em lesões nos membros inferiores - Santos, Paulo José Moraes de Paula [UNESP] (2015)
Karate is a sport still on the rise. In this study, the implication of karate blow was evaluated using biomechanical principles. One of the purposes is to help in the epidemiology of injuries in sports and in karate, the front kick is one of the most used strokes, while at the same time, the legs were the most affected sites due to injuries. The aim of this study was to correlate the peak acceleration of the movement and its implications for the injury in the lower limbs in karate and to verify the performance of the Straight femoral muscles during blow execution. This work studies the technical front kick Mae Geri, through the kinematics of Electromyography and data peak Bang acceleration. The collection was carried out in the laboratory with 8 athletes, 7 males and 1 female. Each practitioner held 10 and 5 in a static position and 5 in dynamic position. The acceleration was detected by an accelerometer coupled to a protected steel plate fixed to a metal frame adjusted to the athlete's height. The results were compared with data in the literature on the relationship between peak acceleration and the way that injuries occur. Thus, the present study found that the front kick studied develops a great acceleration, which is not necessarily linked to the weight of the subject, and may be detrimental to practitioners of the embodiment, moreover, the RMS values obtained by analysis of the electromyographic Straight femoral link not necessarily the most kick that orders the muscle is one that will develop greater acceleration